Symposium 4: Practitioner research as experiential learning? The case of COLMSCT - Hills, Laura; Swithenby, Steve (Proceedings of the International Conference on Networked Learning, 2010)
Practitioner research is now long established as a means of professional development for academics in higher education, resulting in well documented benefits for the practitioner researcher and their students. What is less well documented is the process by which individual academic members of staff develop as practitioner researchers and how their engagement with the realities of practice and research influences their learning. This paper is a case study of professional development through practitioner research at the Centre for Open Learning in Mathematics, Science, Computing and Technology (COLMSCT) at the Open University, UK. COLMSCT was established in 2005 to reward teaching excellence and to fund practitioner research into develop ‘effective and engaging’ ways of using new technologies to support students at a distance. A total of 63 two-year projects have been supported through COLMSCT, involving both full-time academics and part-time distance tutors. The effects of the practitioner research projects have been evidenced at the level of student experience, personal transformation, colleagues, the institution and the wider higher education sector and include: changes in individual practice, increased involvement in research, modifications to assessment at module and programme level, and conference presentations and journal publications. The paper uses the theory of experiential learning, and in particular Kolb’s learning cycle, to explore the process of professional development through practitioner research. Kolb’s phases of learning, namely concrete experience, reflective observation, abstract conceptualization and active experimentation, are used as a lens through which to examine the process and effects of practitioner research on the individual, their students and the wider institutional and higher education context. The paper provides examples of how the processes and effects of practitioner research, such as observing practice, engagement with theoretical approaches and implementing change, relate to these phases of learning. It also demonstrates that when these phases interact, so when practitioner researchers bring abstract concepts or theoretical insights into their observations of practice, transformation, or learning, occurs. It examines the factors which influence this learning and concludes that the professional development opportunities provided by practitioner research are, in part, determined by the role that the individual practitioner researcher occupies in the ‘outside world’ of practice.